Psychometric properties of full WHODAS 2.0 questionnaire for application through phone surveys: an experience in PERSIAN traffic cohort - Shahedifar, Nasrin; Sadeghi-Bazargani, Homayoun; Golestani, Mina; Asghari Jaafarabadi, Mohammad; Pourasghar, Faramarz; Bazargan-Hejazi, Shahrzad (Springer Science and Business Media LLC, 2025)
Introduction
To promote trauma survivors’ care quality, assessment of their disability is essential. This study assessed psychometric characteristics of World Health Organization disability assessment schedule (WHODAS 2.0) and its applicability in screening via phone survey through advanced methods.
Methods
We recruited 321 adult patients within a national PERSIAN Traffic Cohort: post-crash phase. They completed 36-item WHODAS 2.0. The translation validity– with WHO permission– was examined. The confirmatory factor analysis (CFA) tested the dimensionality, reliability and validity using smart partial least squares structural equation modeling. Item properties – discrimination, difficulty, and differential item functioning – were assessed with the item response theory-graded response model. Test-retest reliability was evaluated by retesting 40 participants after 9 days.
Results
The majority of 321 respondents were men (72%) or employed (75%). The mean age was 40.3(SD=13.4;19- 70yrs.). The translation validity was supported. CFA confirmed convergent validity, discriminant validity, predictive accuracy, predictive relevance, and predictive quality. The composite reliability, Cronbach’s alpha (0.94-0.95) and rho-A, intra class correlation coefficient, and weighted Kappa coefficient supported reliability. The 6-factor model showed sufficient fit (GoF=0.58). Discrimination parameters distinguished respondents by disability levels, except for three items. The test characteristic and information function curves illustrated items’ difficulty shifting toward higher disability level. Two items specified significant differential functioning by sex.
Discussion
The findings support reliability and validity of the Persian WHODAS 2.0. The findings demonstrate that the measure is especially apt at distinguishing higher-levels of disability. This highlights the tool's value in generating functional profiles to assess disability among trauma survivors in both clinical and research settings.